Interactions between global change and multiple infection have complex effects on life-history traits of Daphnia magna and its parasites - O'Keeffe, Floriane Elisa (Trinity College Dublin. School of Natural Sciences. Discipline of Zoology, 2024)
Recent outbreaks of disease such as the COVID-19 pandemic have highlighted the need to better understand the drivers of pathogen spread and transmission, especially with disease outbreaks becoming more frequent due to anthropogenic change. Global warming frequently alters the outcome of disease, either increasing or decreasing it, but although studies often focus on constant rising temperatures, climate change is also exacerbating temperature variability and increasing the frequency of extreme weather events such as heatwaves, both of which may have complex impacts on parasites and their hosts. Additionally, rising global temperatures may be accompanied by other ecological changes, such as eutrophication due to increased nutrient concentrations in the environment. The outcome of parasitic infections from combined impacts of temperature and nutrient stress is difficult to predict, especially in cases where the two stressors interact, and seems to be specific to the host-parasite system. Furthermore, although much of the research investigating how diseases respond to changing ecological parameters focuses on single parasites and their hosts, multiple infections with two or more parasites are common in real-world systems, and may add another layer of complexity when trying to make generalisations about the consequences of global change on disease. In this thesis, I use an empirical approach combined with Bayesian modelling to investigate how the parasites of the freshwater invertebrate Daphnia magna respond to increasing temperatures and temperature variability, changes in nutrient levels combined with rising constant temperatures, and multiple infection under a scenario of increasing temperatures and heatwave conditions. My results show that different parasites have differing thermal tolerance, but that the breadth of these temperature ranges does not allow for predictions of parasite response to temperature variation and heatwaves. Moreover, I find that increasing temperatures and changing nutrient levels have strong individual effects on infection in a Daphnia-microsporidian system, but may also interact leading to varying responses in parasite life-history traits. Finally, I observe that despite the absence of prior residency effects on co-infection in this system, varying temperatures lead to changes in the outcome of multiple infection at the extremes of the Daphnia thermal range. I conclude that these findings add to the growing number of studies which suggest that the outcome of disease under conditions of climate change may be system-specific, and suggest that predictions may be harder to draw than anticipated due to the complexity of the many factors at play.
APPROVED
Keywords: disease ecology; epidemiology; daphnia; freshwater; parasitology; climate change; multiple infection; global warming